PTH Immunoassay Interference Due to Human Anti-Mouse Antibodies in a Subject With Obesity With Normal Parathyroid Function - Laudes, Matthias; Frohnert, Janosch; Ivanova, Kamelia; Wandinger, Klaus-Peter (The journal of clinical endocrinology and metabolism, 2019)
Immunoassay interference has been most often found with prolactin measurement. However, only few data exist on immunoassay interference for other hormones. A 36-year-old woman with obesity (body mass index, 31 kg/m2) had regularly attended our endocrine unit for type 2 diabetes therapy. When she was included as a control subject in a study for obesity management, detailed laboratory testing was performed, including PTH. In the absence of clinical symptoms, she presented with normal calcium, phosphate, and vitamin D levels. However, the PTH levels were >5000 ng/L. These results were obtained using the Roche Elecsys electrochemiluminescence assay. Repeated measurements with this assay (mouse antibody) led to the same findings. However, using an Euroimmun assay (goat antibody), the exact PTH values were measured at 18.0 ng/L. After pretreatment with a heterophilic antibody blocking reagent, the results of the Roche assay had decreased to a normal level. This phenomenon was explained by the detection of human anti-mouse antibodies in the proband's serum. In cases of prolactin immunoassay interference, endogenous antibodies will bind to the hormone in vivo, resulting in complexes of a high molecular weight that are less efficiently cleared by the kidneys and, thus, accumulate in the blood. In contrast, the PTH values >5000 ng/L detected in our subject most likely had resulted from the specific interference of the human anti-mouse antibodies present in the proband's serum with the assay antibody, resulting in artificial stimulation of the Roche assay detection system ex vivo.